Safety critical software ground rules - Chaya Addagarrala, Krishna; Kinnicutt, Patrick (International Journal of Engineering and Technology, 2018)
Safety critical software development field is one of the active research areas in many industries like automotive, medical, railways, nuclear and aerospace are placing increased value on safety and reliability. Safety critical software systems are those systems whose failure could result in the death or a serious injury to the peopleâ€™s life, security is one of the important topics in the field of safety-critical systems and it must be addressed completely in order to operate safety critical software successfully. In this paper we present a study about the set of standards and different ground rules to be followed in critical software development practices in different industries and the challenges in applying these standards. We also discuss the role of static analysis and software integrity levels in these standards, similarities in these standards and the set of activities followed in the development process of these standards.Â